Motivations and management factors of volunteer work in nonprofit organisations: a literature review - Ferreira, Marisa R. (2013)
The objective of this paper is to review and discuss the literature about volunteers’ motivations to donate their time to NPOs and the management factors that can influence volunteer work. Firstly, the paper illustrates and compares the different types of motivation followed by a presentation of a typology that organises the volunteers’ motivations into four types: (i) altruism, (ii) belonging, (iii) ego and social recognition and (iv) development and learning. Secondly we discuss the key management factors in volunteering: recruitment, training and rewarding. Finally, we present four gaps in the literature that justify the scope for further research: (i) omission of differences between motivations related to volunteers’ "Attraction" versus "Retention"; (ii) focus of the research on the USA, UK and Australia context; (iii) absence of comparative analyses that relate motivations by NPO types and (iv) comprehension of how management factors (recruitment, training and rewarding) influence volunteers’ satisfaction and retention.